The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cells11233861
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β2 Regulates Transcription of the K+/Cl− Cotransporter 2 (KCC2) in Immature Neurons and Its Phosphorylation at T1007 in Differentiated Neurons

Abstract: KCC2 mediates extrusion of K+ and Cl− and assuresthe developmental “switch” in GABA function during neuronal maturation. However, the molecular mechanisms underlying KCC2 regulation are not fully elucidated. We investigated the impact of transforming growth factor beta 2 (TGF-β2) on KCC2 during neuronal maturation using quantitative RT-PCR, immunoblotting, immunofluorescence and chromatin immunoprecipitation in primary mouse hippocampal neurons and brain tissue from Tgf-β2-deficient mice. Inhibition of TGF-β/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…1). This lack of effect can be attributed to the presence of endogenous TGF-β2, which may saturate the signaling pathway, similar to what was previously observed on KCC2 expression (Rigkou et al, 2022). Subsequent loss-of-function experiments in brain areas at different maturation stages in Tgf-β2 mutants and expression analysis of multiple transcript variants of Ank3 , showed no regulation in the forebrain of Tgf-β2 mutants (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…1). This lack of effect can be attributed to the presence of endogenous TGF-β2, which may saturate the signaling pathway, similar to what was previously observed on KCC2 expression (Rigkou et al, 2022). Subsequent loss-of-function experiments in brain areas at different maturation stages in Tgf-β2 mutants and expression analysis of multiple transcript variants of Ank3 , showed no regulation in the forebrain of Tgf-β2 mutants (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…We next investigated whether loss of the TGF-β2 ligand affects Ankyrin-G expression, using Tgf-β2 deficient mice at E17.5. We have previously demonstrated that the impact of TGF-β2 on KCC2 varies between the embryonic forebrain and brainstem, presumably due to differences in neuronal maturation (Rigkou et al, 2022). Here, we followed the same principal to investigate a potential differential regulation of Ankyrin-G by TGF-β2 in forebrain and brainstem.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β2 enhanced the colocalization and interaction between KCC2 and Rab11b, and impairing CREB1 or Rab11b hindered TGF-β2-mediated trafficking, surface expression, and functionality of KCC2. In a recent study, Rigkou et al examined the effects of TGF-β2 on KCC2 during neuronal maturation [ 92 ]. They found that inhibiting TGF-β/activin signaling decreased KCC2 mRNA expression in immature neurons.…”
Section: Posttranslational Regulatory Mechanisms Of Kcc2mentioning
confidence: 99%